The Changing Occupational Structure of Large Metropolitan Areas: Implications For The High School Educated. - Skinner, Curtis (Journal of Urban Affairs, 2004)
This article examines employment trends in broad occupational categories during the 1986 to 1999 period for a group of 50 large United States metropolitan areas. after describing the secular trends, I estimate a cross-sectional model to quantify the effects of local industry mix and labor-saving technology on the occupational employment distribution in these urban areas. Despite quite heterogeneous occupational employment distributions among the 50 MSAs, I find a strikingly uniform decline in the share of mid-skilled administrative support and precision production, craft and repair occupations appropriate for high school graduates and growth in the share of high-skilled managerial and professional occupations, suggesting skill and wage polarization. The regression analysis indicates that the share of mid-skilled employment in large metropolitan areas is positively associated with the output shares of the durable manufacturing and finance, insurance and real estate (FIRE) industries and negatively associated with the introduction of labor-saving technologies in these industries. I conclude by reviewing local policy initiatives that may improve labor market outcomes for high school graduates. Reprinted by permission of the publisher.